Unveiling the mechanism of action of acylated temporin L analogues against multidrug-resistant Candida albicans - Rosa Bellavita; Annarita Falanga; Francesco Merlino; Gabriella D'Auria; Nicola Molfetta; Anella Saviano; Francesco Maione; Umberto Galdiero; Maria Rosaria Catania; Stefania Galdiero; Paolo Grieco; Emanuela Roscetto; et al. (Taylor & Francis Group, 2023)
The increasing resistance of fungi to conventional antifungal drugs has prompted worldwide the search for new compounds. In this work, we investigated the antifungal properties of acylated Temporin L derivatives, Pent-1B and Dec-1B, against Candida albicans, including the multidrug-resistant strains. Acylated peptides resulted to be active both on reference and clinical strains with MIC values ranging from 6.5 to 26 µM, and they did not show cytotoxicity on human keratinocytes. In addition, we also observed a synergistic or additive effect with voriconazole for peptides Dec-1B and Pent-1B through the checkerboard assay on voriconazole-resistant Candida strains. Moreover, fluorescence-based assays, NMR spectroscopy, and confocal microscopy elucidated a potential membrane-active mechanism, consisting of an initial electrostatic interaction of acylated peptides with fungal membrane, followed by aggregation and insertion into the lipid bilayer and causing membrane perturbation probably through a carpeting effect.